Biventricular Cardiac Resynchronization Therapy with Atrial Sensing but No Atrial Lead: A Prospective Registry of Patients, Complications, and Therapy Responses - Kolb, Christof; Zima, Endre; Arnold, Martin; Fedorco, Marián; Bonnemeier, Hendrik; Deneke, Thomas; Schumacher, Burghard; Nordbeck, Peter; Steinwender, Clemens; Storz, Theresa; Merkely, Béla; Anneken, Lars; et al. (Journal of clinical medicine, 2025)
Background/Objectives: Patients with normal sinus rhythms undergoing cardiac resynchronization therapy defibrillator (CRT-D) implantation may benefit from a novel two-lead CRT-D system (CRT-DX), which features an atrial sensing dipole integrated into the right ventricular lead. This single-arm, international, non-controlled investigation focused on the safety and clinical efficacy of CRT-DX devices in CRT-D candidates who do not require atrial pacing. Methods: Patients indicated for CRT-D implantation (resting heart rates > 40 bpm and ≥100 bpm during exercise, no second or higher-degree AV block, and no history of persistent or permanent atrial fibrillation) were enrolled across 21 sites in four European countries. The primary endpoint was the need for an additional RA lead implantation within 12 months. Secondary endpoints comprised any invasive re-intervention to the CRT-DX system or infection. Results: Among the 110 patients (mean age 62 years, 70% male), 60% had an underlying non-ischemic cardiac disease. During 12 months of follow-up, RA lead implantation was required in two patients for atrial undersensing or chronotropic incompetence (RA lead implantation-free rate: 98.2% (95% CI: 92.7-99.5%)). Atrial sensing amplitudes were stable (mean: 4.7 ± 1.7 mV), AV-synchrony was maintained at >99%, and the median percentage of biventricular pacing exceeded 98%. The left ventricular ejection fraction improved by an absolute 14.7%. Conclusions: Using simple, clinically applicable inclusion criteria, the two-lead CRT-DX system demonstrated a low rate of subsequent RA lead implantations (1.8%) and maintained adequate RA sensing amplitudes throughout the observation period. The two-lead CRT-DX concept appears to be a feasible alternative for patients with preserved chronotropic competence.
Keywords: safety; atrial floating sensing dipole; CRT-DX; two-lead CRT-D; patient selection; cardiac resynchronization therapy